2009
DOI: 10.1002/pssa.200925208
|View full text |Cite
|
Sign up to set email alerts
|

Determination of levitation force and pinning properties of (Sm123)1−x(Yb211)x bulk superconductor depending on Yb211 doping ratio

Abstract: The vertical force density curves of (Sm123)1−x(Yb211)x high temperature superconductor (HTS) samples prepared by a melt‐powder‐melt‐growth technique were measured during vertical and lateral traverses in zero field cooling (ZFC) regime for various doping levels (x). It was determined that the maximum vertical force density of the samples increases when the doping level increases and after certain level of the doping the force saturates. The pinning properties, which create attractive force, were enhanced up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 52 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Following this procedure, Yb211-doped and undoped powders are pressed into a pellet form with 13 mm in diameter under 400 MPa pressure. Then, to understand whether the reheating temperature and cooling speeds have an effect on superconducting levitation force or not (Sm123)1−x(Yb211)x samples are heated to 1170 • C (reheating temperature) which is different than our earlier produced Sm123 samples [26]. After that, the samples were held at this temperature for 15 min and cooled down to 980 • C at the speed of 1.7 • C/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this procedure, Yb211-doped and undoped powders are pressed into a pellet form with 13 mm in diameter under 400 MPa pressure. Then, to understand whether the reheating temperature and cooling speeds have an effect on superconducting levitation force or not (Sm123)1−x(Yb211)x samples are heated to 1170 • C (reheating temperature) which is different than our earlier produced Sm123 samples [26]. After that, the samples were held at this temperature for 15 min and cooled down to 980 • C at the speed of 1.7 • C/min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the understanding and control of the microstructure are attractive challenges to enhance the superconducting properties of MPMG-processed Sm123 sample. Our previous studies indicated that the doping of Yb211 (Yb 2 BaCuO 5 ) into the Sm123 superconductor sample increases the value of the vertical magnetic levitation force [26]. The main objective of this study is to determine the relations between critical current density, volume magnetic pinning force, magnetic levitation force (in zero field cooling regime) and pinning mechanism of the bulk superconductor samples with nominal composition of (Sm123) 1−x (Yb211) x depending on non-superconducting Yb211 doping ratio x, varying from 0.00 to 0.35.…”
Section: Introductionmentioning
confidence: 99%
“…Although some advancements have been achieved in improving the flux pinning ability and critical current density of HTS [11,12], the levitation [13] and guidance force values of HTS Maglevs are still mostly far from the technological applications. Also the production cost is very important issue to be taken into account for industrial application in Maglev systems.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on bulk high temperature superconductors (HTS) indicate that the properties such as trapped magnetic field, magnetic levitation force and critical current density can be improved considerably by introducing nanometer-scale weak superconducting regions and by improving material processing techniques [12,13]. Since the discovery of superconductivity in bulk MgB 2 , it has been proposed as an alternative to HTS for these applications as, despite its lower critical temperature of 39 K, it has superior mechanical and superconductive properties.…”
Section: Introductionmentioning
confidence: 99%